Pengaruh Penerapan Prinsip- Prinsip Ekonomi Syariah Terhadap Kinerja Keuangan Perbankan Islam - Novianto, Satrio; Nisa, Fauzatul Laily (Ikatan Da'i Indonesia, 2024)
The application of sharia economic principles in Islamic banking has a significant impact on banking financial performance. This research discusses how the implementation of sharia economic principles in Islamic banking can improve banking financial performance. The research results show that Islamic banking which applies sharia economic principles has better financial performance compared to conventional banking. Sharia economic principles such as ethical risk management, development of Islamic capital markets, and community economic empowerment contribute to improving the financial performance of Islamic banking. In synthesis, this research shows that the application of sharia economic principles in Islamic banking can improve banking financial performance and increase public awareness about the importance of sharia economic principles in financial management.